Production of Clean Energy by Green Ways - Singh, D (Elsevier, 2018)
Energy is the most basic requirement for the existence of life on earth. It is an integral part of daily life, from our rising in the morning to going to bed at night. Energy requirements are increasing day by day due to improvements in the quality of life. All sectors are dependent on energy, from industry and transportation to the myriad comforts and conveniences of the home and workplace, and even national security. Our appetite for energy has become boundless. However, energy sources are circumscribed (~85% of total energy is derived from fossil fuels like oil, coal, and gas), as usage of fossil fuels occurs much faster than they are formed. Development has been directly correlated with increased use of fossil fuels (source of energy), with worldwide demand estimated to double by 2030. Thus, there is an urgent need to look for some long lasting substitutes which could fulfill our energy demands in an economical way. © 2019 Elsevier Inc. All rights reserved.